2021
DOI: 10.1039/d0tc06044e
|View full text |Cite
|
Sign up to set email alerts
|

Self-sintering liquid metal ink with LAPONITE® for flexible electronics

Abstract: Liquid-metal (LM)-based flexible and stretchable electronics have attracted widespread interest in soft robotics, self-powered devices and electronic skins. Although nanometerization can facilitate deposition and patterning of LMs onto substrates, subsequent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…What is more, we found that the force that causes the rupture of the alginate networks can be generated not only externally but also from the inside out. Unlike common hard metals, liquid metals will undergo a phase change from liquid to solid at low temperatures, just like water, leading to volume expansion behavior. ,, Based on this, the volume expansion of LM microdroplets caused by freezing can also squeeze the dehydrated alginate networks wrapped around them and cause the fusion of the LM droplets. The processes of pressing activation and freezing activation circuits are shown in Movies S4 and S5 in the Supporting Information, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, we found that the force that causes the rupture of the alginate networks can be generated not only externally but also from the inside out. Unlike common hard metals, liquid metals will undergo a phase change from liquid to solid at low temperatures, just like water, leading to volume expansion behavior. ,, Based on this, the volume expansion of LM microdroplets caused by freezing can also squeeze the dehydrated alginate networks wrapped around them and cause the fusion of the LM droplets. The processes of pressing activation and freezing activation circuits are shown in Movies S4 and S5 in the Supporting Information, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Conventional rigid electronics exhibiting poor flexibility and compliance cannot meet the requirements of advanced wearable devices that usually need to withstand large deformations or work on nonplanar surfaces. , In recent years, gallium-based liquid metals (LMs), as fluid soft materials with superb metallic conductivity, have drawn tremendous attention and have been employed to manufacture flexible electronics, including electronic skin, , energy-harvesting devices, , wearable health monitoring equipment, , 3D circuits and nanotips, , and more. Additionally, unlike toxic mercury, LMs possess negligible toxicity and low vapor pressure, making them ideal conductive components in flexible electronics in close contact with skins. , To date, numerous trials based on additive manufacturing have been adopted to prepare conductive liquid metal patterns for specific electrical functions, including stamp printing, , masked deposition, , inkjet/spray printing, , direct writing, and so forth. However, limited by its own huge surface tension and strong fluidity, LM tends to aggregate into intermittent low-surface-energy spheres rather than forming desired continuous patterns during processing, , making it challenging to directly pattern pure liquid metal into desired circuits with high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the melting point temperature of gallium-based alloys such as gallium indium alloy (EGaIn), gallium tin alloy (EGaSn), and gallium indium tin alloy (EGaInSn, Galinstan) can be regulated by changing the proportion of alloy components. These unique properties of gallium-based LMs make them have wide application potential in soft electronics, ,, flexible devices, , biological devices, , thermal management, , and nuclear industry. , …”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, the melting point temperature of gallium-based alloys such as gallium indium alloy (EGaIn), 8 gallium tin alloy (EGaSn), and gallium indium tin alloy (EGaInSn, Galinstan) can be regulated by changing the proportion of alloy components. These unique properties of gallium-based LMs make them have wide application potential in soft electronics, 1,9,10 flexible devices, 11,12 biological devices, 13,14 thermal management, 15,16 and nuclear industry. 17,18 Gallium-based LMs are highly susceptible to oxidation when exposed to air, forming a dense thin film of gallium oxide, which prevents further oxidation of internal gallium 1,19 while reducing the surface tension, 20 thermal conductivity, and conductivity of LM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these nanomaterials, Laponite (Lap) as a synthetic and biodegradable hydrous magnesium lithium silicate has the empirical formula Na + 0.7 [(Mg 5.5 Li 0.3 )Si 8 O 20 (OH) 4 ] − 0.7 ). [24] Polymer chains can physically crosslinked to the surface of clay nanosheets through ionic or polar interactions resulting in unique organic/inorganic networks. [25] Besides, the ions released from the exfoliated clay nanosheets give conductivity to gels.…”
Section: Introductionmentioning
confidence: 99%